Harmonic Response Analysis of RV Reducer - Wu Suzhen; Guo Yi; Tian Yu (Jixie chuandong, 2016)
The cycloid gear and the crankshaft are important parts of a RV reducer,and the bending deformation at Rome dots of the component is one of the main failure forms of the RV reducer. Therefore,taking the RV- 250 reducer as the research object,and the RV- 250 reducer model without interference is built.Based on the characteristic of periodic input,uing the finite element method,the harmonic response analysis of RV reducer is completed and the amplitude frequency response curve of the eccentric shaft and the cycloid gear of the key components are obtained,as well as the index of dynamics such as natural frequency and the response amplitude. Results show that it will lead to the cycloid gear bending vibration and axial deformation when the vibration force of eccentric shaft is around 360 Hz,a theoretical basis for the optimal design of the cycloid gear and the crankshaft is provided.